Thermoeconomic analysis of an integrated solar combined cycle power plant. (1st September 2018) - Calise, Francesco; d'Accadia, Massimo Dentice; Libertini, Luigi; Vicidomini, Maria
Highlights: A dynamic simulation model of an integrated solar combined cycle is presented. Triple pressure combined cycles are coupled with parabolic trough collectors. A novel control strategy is adopted to limit the steam turbine off-design operation. System economic performance is acceptable only in case of public funding. Plant overall electrical efficiency is increased of about 1%. Abstract: In this work, a dynamic model of a high-temperature integrated solar combined cycle power plant is presented. The system includes a three-pressure combined cycle power plant coupled to parabolic trough solar collectors. Thermal storage, a heat solar steam generator, pumps, heat exchangers, and several controllers are also included in the system. Solar energy is used to produce additional steam to be supplied to the steam turbine of the combined cycle power plant. The integrated solar combined cycle system is based on the heat transfer fluid arrangement, exploiting solar energy to produce steam. The analysis is developed by a dynamic simulation model including detailed algorithms for the calculation of the performances of system components. Special control strategies are included in the model in order to accurately manage the steam production of the heat solar steam generator. The paper presents a thermo-economic and environmental comparison between the integrated solar combined cycle and a conventional combined cycle, powered by fossil fuels, based on dynamic simulations. A case study, referred to a plant with a maximum power of around 100 MW, located in Almeria (Southern Spain), is presented and discussed. A parametric analysis was also performed to show the effect of the variation of total solar field reflector area on the system performance. For the case under evaluation, a simple pay-back of 15 years was found, for a solar field aperture area of 80 000 m 2 ; however, the parametric analysis suggests that a smallest solar field area should be used under the hypotheses of the case study.